Characteristics, Outcomes, and Predictability of Critically Ill Obstetric Patients: A Multicenter Prospective Cohort Study. Issue 9 (September 2015) - Vasquez, Daniela N.; Das Neves, Andrea V.; Vidal, Laura; Moseinco, Miriam; Lapadula, Jorge; Zakalik, Graciela; Santa-Maria, Analía; Gomez, Raúl A.; Capalbo, Mónica; Fernandez, Claudia; Agüero-Villareal, Enrique; Vommaro, Santiago; et al.
Abstract : Objective: To evaluate pregnant/postpartum patients requiring ICUs admission in Argentina, describe characteristics of mothers and outcomes for mothers/babies, evaluate risk factors for maternal-fetal-neonatal mortality; and compare outcomes between patients admitted to public and private health sectors. Design: Multicenter, prospective, national cohort study. Setting: Twenty ICUs in Argentina (public, 8 and private, 12). Patients: Pregnant/postpartum (< 42 d) patients admitted to ICU. Interventions: None. Measurements and Main Results: Three hundred sixty-two patients were recruited, 51% from the public health sector and 49% from the private. Acute Physiology and Chronic Health Evaluation II was 8 (4–12); predicted/observed mortality, 7.6%/3.6%; hospital length of stay, 7 days (5–13 d); and fetal-neonatal losses, 17%. Public versus private health sector patients: years of education, 9 ± 3 versus 15 ± 3; transferred from another hospital, 43% versus 12%; Acute Physiology and Chronic Health Evaluation II, 9 (5–13.75) versus 7 (4–9); hospital length of stay, 10 days (6–17 d) versus 6 days (4–9 d); prenatal care, 75% versus 99.4%; fetal-neonatal losses, 25% versus 9% ( p = 0.000 for all); and mortality, 5.4% versus 1.7% ( p = 0.09). Complications in ICU were multiple-organ dysfunction syndrome (34%), shock (28%), renal dysfunction (25%), and acute respiratory distress syndrome (20%); all predominated in the public sector. Sequential Organ Failure Assessment (during first 24 hr of admission) score of at least 6.5 presented the best discriminative power for maternal mortality. Independent predictors of maternal-fetal-neonatal mortality were Acute Physiology and Chronic Health Evaluation II, education level, prenatal care, and admission to tertiary hospitals. Conclusions: Patients spent a median of 7 days in hospital; 3.6% died. Maternal-fetal-neonatal mortality was determined not only by acuteness of illness but to social and healthcare aspects like education, prenatal control, and being cared in specialized hospitals. Sequential Organ Failure Assessment (during first 24 hr of admission), easier to calculate than Acute Physiology and Chronic Health Evaluation II, was a better predictor of maternal outcome. Evident health disparities existed between patients admitted to public versus private hospitals: the former received less prenatal care, were less educated, were more frequently transferred from other hospitals, were sicker at admission, and developed more complications; maternal and fetal-neonatal mortality were higher. These findings point to the need of redesigning healthcare services to account for these inequities.